LncRNA FUNDC2P4 down-regulation promotes epithelial–mesenchymal transition by reducing E-cadherin expression in residual hepatocellular carcinoma after insufficient radiofrequency ablation. (18th August 2018) - Zeng, Jiangzheng; Cai, Xinrui; Hao, Xinbao; Huang, Fen; He, Zhihui; Sun, Huamao; Lu, Yanda; Lei, Junhua; Zeng, Wangyuan; Liu, Yu; Luo, Rongcheng
Abstract: Purpose: Hepatocellular carcinoma (HCC) after insufficient radiofrequency ablation (RFA) could induce epithelial–mesenchymal transition (EMT) in residual tumours, resulting in rapid and aggressive recurrence. However, the role of EMT-related Long noncoding RNAs (lncRNAs) in residual tumour progression remains unclear. Methods: Insufficient RFA was simulated in vitro by heating Huh7 cells in water bath at 47 °C, named as Huh7-H. Cell invasion, migration assays and wound healing assay were conducted for functional analysis. Cell proliferation was determined by CCK8 assay. Differential expression profile of EMT-related lncRNAs between Huh7-H and Huh7 was analysed by LncPath human EMT array, and validated by qRT-PCR. Gain/loss-of-function assays of selected lncRNA were conducted by over-expressing or silencing its expression. Results: Huh7-H presented characteristic EMT morphological changes. WB analysis showed significantly decreased E-cadherin in Huh7-H cells. Transwell assays indicated the abilities of Huh7-H cells in migration and invasion were evidently strengthened. A new lncRNA, FUNDC2P4, was identified by LncPath human EMT array to be significantly down-regulated in Huh7-H cells. In vitro studies showed overexpression of FUNDC2P4 inhibited proliferation, invasion and migration potential and up-regulated E-cadherin expression in SMMC-7721 cells, whereas silencing FUNDC2P4 promoted these potentials and down-regulated E-cadherin expression in Huh7 cells. Conclusions: We explored that lncRNA FUNDC2P4 down-regulation promoted EMT leading to tumour proliferation, invasion and migration by reducing E-cadherin expression in residual HCC after insufficient RFA in vitro . These results suggest that FUNDC2P4 may have potentially therapeutic value for prevention and treatment of HCC recurrence after RFA in the future.